Integrasi Teknologi Digital dan OpenCart sebagai Solusi Inovatif untuk Meningkatkan Efisiensi Operasional UMKM di Kabupaten Labuhanbatu - Fattahul Safti Hasibuan, Asyahri; Annas, Firdaus; Rival, Muhammad (Yayasan Lembaga Studi Makwa, 2024)
This article aims to explore the integrity of digital technology and the use of the OpenCart platform as an innovative solution to improve the operational efficiency of MSMEs in Labuhanbatu Regency. MSMEs in this area often face problems in terms of performance control, marketing, and limited market access. These obstacles trigger the failure of MSMEs to compete optimally in an increasingly digital market. MSMEs in Labuhanbatu should be able to utilize digital technology, especially e-commerce platforms such as OpenCart, to increase operational efficiency, expand market reach, and increase the competitiveness of existing products. However, many MSMEs have difficulty accessing and utilizing this technology due to the lack of knowledge and resources controlled by MSME actors. The methodology used in this study is the Research and Development (R&D) method with the PPE (Planning, Production, Evaluation) development stages. The stages of the methodology in this study begin by describing the problems encountered by MSMEs, continuing with designing appropriate solutions, developing significant technology implementations, and finally disseminating research results to improve the interpretation and adoption of technology in MSME groups. The results of the study emphasize that OpenCart integrity can improve the operational efficiency of MSMEs, especially in terms of inventory management, product marketing, and sales transactions. Additional findings include the importance of training for MSMEs to improve knowledge about the use of digital technology and maximize e-commerce platforms in achieving the best profits. Thus, the implementation of digital technology and OpenCart in Labuhanbatu Regency has been proven to increase the competitiveness and operational efficiency of MSMEs, thereby opening up wider and more sustainable market opportunities.